Recent progress on rubber based biocomposites: From carbon nanotubes to ionic liquids - Khan, I. (Springer Verlag, 2017)
Currently, reinforcement of a polymer matrix via the integration of fillers is a common industrial exercise which improves the properties of the composite material. Rubber nanocomposites (NCs) demonstrated remarkable properties due to the interaction between the polymer and filler and the homogeneous dispersion of the filler within the polymer matrix. These improved properties included increased stiffness, high strength, reduced elongation to failure, improved resistance to crack growth and tearing and finally various modifications of abrasion, dynamic and fatigue properties, due to their high surface area and significant aspect ratios. Different reinforcing fillers have been incorporated in the rubber to develop elastomeric composites having improved properties. This current chapter focus on development, properties and applications of various elastomeric composites. Secondly, this chapter also emphasis on ionic liquids (ILs) role as additives in elastomer composites as well as effects of nanofillers on elastomer composites. © Springer International Publishing AG 2017.